Concentración de la tierra en Colombia (2011)
This article includes results of the study of concentration of land ownership in Colombia. Initially, theoretical aspects are considered related to the Lorenz curve and Gini coeﬃcient computation. Then, a descriptive analysis of the concentration of land ownership, establishing the relationship between owners percentages and percentage of accumulated land. Finally, we present the Gini results by region and department for the year 2000.